Religious institutions and practice of a Malay Community in transition. - Abdul Maulud Yusof (Universiti Kebangsaan Malaysia, 1977)
This first part of this paper discusses the development of social anthropology, particularly the works of social anthropologists who have studied contemporary Malay society and culture. The writer himself focuses his interest on one phenomenon of Malay culture, that is the growth of urban elements in and around Malay culture. Since urbanism has started to influence traditional Malay culture, the writer attempts in the second part of the paper to discuss the activities of a traditional Malay community regarding their religious system, and customs which are related to that religious system. The writer observes that these activities constitute adaptive measures of a traditional community in a new environment.